Local lives, parallel histories villagers and everyday life in the divided Germany - Thomas, Marcel 1991- (Studies in German history, 2020)
Thirty years after German reunification, we still know little about what division meant to Germans who lived far from divided Berlin or the inner-German border. This work uses oral history interviews and archival evidence to compare how villagers in East and West experienced the two very different social and political systems in their localities